What is policy content and how is the public's policy support? A policy cognition study based on natural language processing and social psychology - Zhou, Lingyi; Dai, Dingzhang; Ren, Junxia; Chen, Xiaoxu; Chen, Siming (Frontiers in Psychology, 2022)
Public policy plays a critical role in coordinating social resources, providing public services, and promoting public values. However, few studies have systematically investigated the public’s policy cognition from the objective aspect of policy content and the subjective aspect of target audience’s policy support. To fill these gaps, we explore the policy content via natural language processing and also policy support from the perspective of social psychology. specifically, regarding the policy content analysis, we collect over one thousand policy documents and design an annotation system by analyzing the policy content, basic structure and text features, and then design a text classification and information retrieval model based on the current Chinese large-scale pre-training model for policy content analysis. Moreover, according to the policy tools identified in content analysis, our paper investigates the audience’s policy support of these tools and its influential factors. Based on a sample of 476 respondents from the whole country, we adopt the ordinary least square method to explore the key factors on policy support for supply, demand and environmental tools from three variables: political trust, policy effectiveness and knowledge of policies. This study contributes to existing literature by forming a structured understanding of public policies and exploring the public’s support of policy tools, which could benefit the practitioners during the policy-making process and also enhance successfully policy implementation.